An empirical study of dynamic profitability determinants of Chinese banks - WANG, HANLIN (2018)
Since 2010, China has been Asia's largest economy and the second largest economy in the world. It is of great significance for Chinese banking industry to maintain the smooth operation of the entire economy. After 1978, Modern Chinese banking system has experienced four rounds of multiple convoluted economic reforms and transformations with the guidance of the Chinese government, with the latest round of reforms is from 2003 onward. The joint-equity reform of state-owned commercial banks and active participation of foreign financial institutions promote the diversification and invigorate the whole banking industry to some degree. However, big state-owned commercial banks (SOCBs) benefit from the over-intervention by government, gaining confidence from the public and making huge profits. Combined with Chinese national conditions, this dissertation tries to examine on the determinants of Chinese bank profitability. This dissertation applies two-step System Generalized Methods of Moment (SGMM) to a balanced bank-level panel data consisting of the data from 300 commercial banks during the period between 2011 and 2017. The statistical results demonstrate that Chinese bank profitability is under the comprehensive influence of internal and external factors. The internal variables consist of bank size, credit risk, liquidity, taxation, capitalization, operating efficiency and non-traditional activity, simultaneously, external determinants contain concentration ratio, GDP growth rate and MSCI Real Estate Index (REI). A set of performance measures including ROAA, ROAE and NIM are selected to comprehensively demonstrate bank performance in our regressing model. As a result, there are some mixed findings among the three measures.